Removable partial prosthesis associated with dental implants: review of the literature - Rocca Camus , Sergio (2023)
Placing implants in an edentulous gap associated with a removable partial denture may be beneficial to improve the biomechanics of free-end prostheses as well as patient satisfaction. The objective of the study was to determine the benefits of the association of dental implants with a removable partial prosthesis in edentulous Kennedy class I and II partials. A bibliographic search was carried out in the PubMed, Scopus and Cochrane Library databases of articles published in English, between the years 2002 to 2023, with the descriptors: “dental implant”, “removable partial denture”, “stress” and “mechanical”. 56 articles were obtained, of which 39 were selected. The selection criteria were determined by the content of the publications under the following evaluation criteria: survival rate of dental implants, patient satisfaction, biomechanics, implant position, implant system. retention/support, complications and clinical protocol. The analysis of the information allows us to conclude that the use of dental implants as distal support at a free end in a removable partial prosthesis greatly benefits the masticatory function, biomechanics, satisfaction or adaptability of the patient with an efficiency of 95%. On the other hand, the appropriate placement technique or implant surgical protocol is important to be successful in the treatment.